2017
DOI: 10.1007/s40139-017-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Craniofacial Disorders in Xenopus

Abstract: Purpose of Review Craniofacial disorders are among the most common human birth defects and present an enormous health care and social burden. The development of animal models has been instrumental to investigate fundamental questions in craniofacial biology and this knowledge is critical to understand the etiology and pathogenesis of these disorders. Recent findings The vast majority of craniofacial disorders arise from abnormal development of the neural crest, a multipotent and migratory cell population. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 111 publications
0
36
0
Order By: Relevance
“…Xenopus has proven to be an invaluable model for the study of human craniofacial development and disorders [22,[44][45][46][47][48][49][50], given the highly conserved developmental pathways that drive neural crest migration, differentiation, and craniofacial morphogenesis between systems. Nonetheless, there are gross morphological differences that prevent some direct correlations.…”
Section: Whs-associated Gene Depletion In X Laevis Almost Certainly mentioning
confidence: 99%
See 1 more Smart Citation
“…Xenopus has proven to be an invaluable model for the study of human craniofacial development and disorders [22,[44][45][46][47][48][49][50], given the highly conserved developmental pathways that drive neural crest migration, differentiation, and craniofacial morphogenesis between systems. Nonetheless, there are gross morphological differences that prevent some direct correlations.…”
Section: Whs-associated Gene Depletion In X Laevis Almost Certainly mentioning
confidence: 99%
“…It is noteworthy that the CNC that give rise to the ceratohyal cartilage in Xenopus will later give rise to far anterior portions of the face, and combine with contributions from the Meckel's cartilage to form some regions of the jaw [51,52], but equivalent human craniofacial structures undergo distinct development [53]. Loosely, the ceratohyal cartilage in X. laevis is formed from CNC of the second PA [44,51]; which in human development will give rise to tissues of the hyoid [53]. Morphological impacts resulting from aberrant development of these tissues, as was shown with either TACC3 or WHSC2 KD (Fig.…”
Section: Whs-associated Gene Depletion In X Laevis Almost Certainly mentioning
confidence: 99%
“…We developed a Xenopus model in which we could study braindependent events in embryogenesis: the brain is removed during early embryonic stages, but the animal can be kept alive and development continues. The ability of this vertebrate, a popular model for numerous biomedical contexts, [27][28][29][30][31][32][33][34] to survive and develop without a brain provides a unique opportunity to understand the role of the brain in diverse systems-level outcomes. Our prior research into brain-dependent developmental signaling revealed that the nascent brain, even before being fully formed, plays an instructive role in patterning somitic muscle and peripheral neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…After the induction and subsequent maintenance, NC cells migrate out of the closing neural tube to specific destinations, where they differentiate into various types of cells and contribute to many tissues, such as the craniofacial structures, dental tissues, the peripheral nervous system, pigment cells, and cardiac tissues (Bronner and Simões-Costa, 2016;Simões-Costa and Bronner, 2015;Stuhlmiller and Garcia-Castro, 2012). In humans, impaired NC development can lead to birth defects that are collectively called neurocristopathies, including craniofacial disorders, congenital heart diseases, and pigment defects (Dubey and Saint-Jeannet, 2017;Vega-Lopez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other common symptoms include congenital heart diseases, pigment defects, and hearing/visual impairment (Snijders Blok et al, 2015;Wang et al, 2018); a recent report also suggests that these patients have high rates of neuroblastoma, a rare NC-derived childhood tumor (Lennox et al). Because this spectrum of non-CNS symptoms is typically caused by impaired NC development (Dubey and Saint-Jeannet, 2017;Vega-Lopez et al, 2018), we hypothesized that DDX3X mutations can lead to not only CNS defects but also neurocristopathies.…”
Section: Introductionmentioning
confidence: 99%